EDUKASI KESADARAN MASYARAKAT MENJAGA DAN MELESTARIKAN HUTAN HUJAN TROPIS PADA MASYARAKAT KOTA BONTANG - Hairunnisa .; Mohammad Mohammad Noor; Sabiruddin .; Kheyene Molekandela Broer (Metacommunication, 2018)
ABSTRACT                  Tropical rainforest is Indonesia's natural potential to be saved. The condition of forests in Indonesia, especially in the town of Bontang, East Kalimantan is of concern. The amount of forest destruction caused by human behavior such as forest fires, illegal logging which will impact on environmental damage and can disrupt human activities. This is a threat to the existence of rain forest rainforest such as loss of function of forest itself. The purpose of this study is to find out what kind of education programs provided by the government to the surrounding community in maintaining the rainforest. Bontang city government focus on providing understanding to the public about the importance of maintaining the existence of tropical rain forests in the city of Bontang. This research uses qualitative approach with interview method and focus group discussion (FGD). Government efforts in pursuing activities to educate many experienced obstacles. Counseling is more focused on how to bring benefits to the community in managing the forest but still maintain the forest resources. Such as rubber planting because rubber can increase people's income. this activity is expected to be effective in involving the community to help the government maintain the tropical rain forest in Bontang city.Keywords:  Tropical Rain Forest, Education, Society.